Parkinson’s Disease - A review on treatment strategies and its advances - Subashini, Raman; Mahmood, Syed; Ayah, R. Hilles; Azizur, Rahman (Universiti Malaysia Pahang, 2020)
Parkinson Disease is an incurable neurological disease which affects the Central Nervous System. It is basically a progressive movement disorder that causes motor and non-motor symptoms. As per reported in Parkinson’s News Today, it is estimated over 10 million people worldwide is affected with Parkinsonism. Eventhough it affects people of elderly age (>50 years old), there are still cases affecting younger generation due to genetic factors and others [1,2]. There are many therapies that has been established since early 70s, however advances in the treatment is crucial to adapt with the seriousness of the cases as it affects daily life of themselves and people around them. A PD patient even suffers into Parkinson’s derived depression or may lead to Alzheimers as well. This review discusses on the current strategies to overcome PD as well as newly improved formulations and other strategies like Deep Brain Stimulation, Focussed Ultrasound Surgery and other treatments.